2016
DOI: 10.1371/journal.pone.0164781
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Hippocampal CA1 Single Neuron Firing and Theta Activity during Associative Learning

Abstract: Hippocampal development is thought to play a crucial role in the emergence of many forms of learning and memory, but ontogenetic changes in hippocampal activity during learning have not been examined thoroughly. We examined the ontogeny of hippocampal function by recording theta and single neuron activity from the dorsal hippocampal CA1 area while rat pups were trained in associative learning. Three different age groups [postnatal days (P)17-19, P21-23, and P24-26] were trained over six sessions using a tone c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…In the physiological setting, the mGluR1-driven changes will, of course, exist alongside other forms of synaptic plasticity. During development, theta activity develops ( Charlesworth et al., 2015 , Kim et al., 2016 ) and will enable NMDAR-dependent LTP. The finding that TBS can also drive a reduction in postsynaptic mGluR1 implies that synapses that undergo LTP will be protected against mGluR1-driven synaptic weakening.…”
Section: Discussionmentioning
confidence: 99%
“…In the physiological setting, the mGluR1-driven changes will, of course, exist alongside other forms of synaptic plasticity. During development, theta activity develops ( Charlesworth et al., 2015 , Kim et al., 2016 ) and will enable NMDAR-dependent LTP. The finding that TBS can also drive a reduction in postsynaptic mGluR1 implies that synapses that undergo LTP will be protected against mGluR1-driven synaptic weakening.…”
Section: Discussionmentioning
confidence: 99%
“…Given the hypothesized role of AS in brain development [1,46], one might expect network interactions to be very different during this sleep state; indeed, in adults, AS specifically enhances theta-dependent synchrony in hippocampal networks [32,67] and, moreover, AS-related theta appears to be causally related to hippocampal-dependent memory consolidation [68]. Here, using infant rats, we found that the state of AS permits the expression of theta-dependent functional connectivity between the hippocampus and RN, perhaps driving activity-dependent developmental plasticity at ages when wake-related expression of hippocampal-dependent learning has yet to emerge [69]. Importantly, given that theta oscillations in the developing hippocampal system are preferentially expressed during AS, we suggest that—under normal conditions— the state of AS promotes maximal theta-dependent coupling among structures within the hippocampal network (including the prefrontal cortex, [24]).…”
Section: Discussionmentioning
confidence: 99%
“…Rayleigh's tests were used to determine whether MUA signals were significantly phase-locked to the theta (4-7 Hz) oscillation [69,89]. For this test, a phase estimate was first assigned to each spike time and a phase histogram (20 degree/bin) was generated for each MUA signal.…”
Section: Star Methodsmentioning
confidence: 99%
“…Therefore, DHPG-induced AMPAR trafficking occurs predominantly at low P(r) synapses because this is where the trigger, mGluR1, is expressed most highly. As theta burst activity develops over the course of development (Charlesworth et al, 2015;Kim et al, 2016), this mechanism may contribute to the emergence of a correlation between P(r) and postsynaptic function at later developmental stages (Kay et al, 2011).…”
Section: Mechanisms Of P(r)-dependent Mglur Activationmentioning
confidence: 99%